The Framework of Maslahah Performa as Wealth Management System and its Implication for Public Policy Objectives - Atika Rukminastiti Masrifah; Achmad Firdaus (Media Syari'ah, 2017)
Muslims are encouraged to plan their lives economically and financially in order to achieve the objectives of Shariah. The intention to conduct Islamic economical and financial planning must be aligned with the application of Maqasid Shariah, which emphasizes on the protection of essential needs of Muslims that include preservation of wealth. Furthermore, goal of wealth management is to achieve falah. Objective of wealth management is to get maslahah. Maslahah based wealth management can be derived from cycle of acquiring and utilizing wealth (Firdaus, 2014). Acquiring wealth can be carried out by fullfilling worship orientation, internal process orientation, talent orientation, learning orientation, customer orientation and wealth orientation. Utilizing wealth can be carried out by allocating asset to wealth orientation, customer orientation, learning orientation, talent orientation, internal process orientation, worship orientation. This study proposes the framework of Maslahah Performa as wealth management system in order to highlight its contribution to more comprehensive, rational and realistic answers to contemporary public policy issues in Islamic economic system and to thereby increase awareness of Maslahah Performa approach in structuring and developing public policy products. For this purpose, the authors examine the position of the Maslahah Performa concept in public policy. They also present the essential elements of Maslahah Performa and explain how this approach may contribute to better solutions for various public policy issues and challenges.